Sirolimus Enhances Cyclosporine A-Induced Cytotoxicity in Human Renal Glomerular Mesangial Cells. (23rd January 2012) - O'Connell, Séin; Slattery, Craig; Ryan, Michael P.; McMorrow, Tara
Abstract : End Stage Renal Disease (ESRD) is an ever increasing problem worldwide. However the mechanisms underlying disease progression are not fully elucidated. This work addressed nephrotoxicity induced by the immunosuppressive agents' cyclosporine A (CsA) and sirolimus (SRL). Nephrotoxicity is the major limiting factor in long term use of CsA. SRL causes less nephrotoxicity than CsA. Therefore investigations into the differential effects of these agents may identify potential mechanisms of nephrotoxicity and means to prevent ESRD induced by therapeutic drugs. Using ELISA, Western blotting, quantitative PCR and a reporter gene assay we detailed the differential effects of CsA and SRL in human renal mesangial cells. CsA treatment increased profibrotic TGF- β 1 secretion in human mesangial cells whereas SRL did not, indicating a role for TGF- β in CsA toxicity. However we observed a synergistic nephrotoxic effect when CsA and SRL were co-administered. These synergistic alterations may have been due to an increase in CTGF which was not evident when the immunosuppressive drugs were used alone. The CsA/SRL combination therapy significantly enhanced Smad signalling and altered the extracellular matrix regulator matrix metalloproteinase 9 (MMP-9). Inhibition of the ERK 1/2 pathway, attenuated these CsA/SRL induced alterations indicating a potentially significant role for this pathway.